DIALEK KHAS DAERAH PERBATASAN: KAJIAN SOSIOLINGUISTIK DI DESA SRINAHAN KECAMATAN KESESI KABUPATEN PEKALONGAN JAWA TENGAH - Didit Kurniadi (Jurnal CULTURE (Culture, Language, and Literature Review), 2018)
Dialect reflects thedaily life of the speaker and becomes the local culture of the people who speak it. This journal contains of the description of a typical dialect of Javanese language in thevillage of Srinahan Kesesi district Pekalongan Central Java Indonesia from sociolinguisticspoint of view. There are many striking differences in dialect used by Srinahan villagers in theborder area of the district and become combination of eastern and western Javanese dialect. Thetypical dialect of Srinahan village community can be seen from the categories of phonology,morphology, and lexical aspects.Keywords: Local Culture, Dialect, Sociolinguistics, Javanese Language.